Acute Effects of Whole-Body Vibration on the Pain Level, Flexibility, and Cardiovascular Responses in Individuals With Metabolic Syndrome - D.C. Sá-Caputo; L.L. Paineiras-Domingos; Ricardo Oliveira; Mario F.T. Neves; Andrea Brandão; Pedro J. Marin; Borja Sañudo; Trentham Furness; Redha Taiar; M. Bernardo-Filho (SAGE Publishing, 2018)
The aim of the study was to assess the acute effect of whole-body vibration (WBV) exercise, with low frequency (5 Hz), on the pain level (PL), trunk flexibility, and cardiovascular responses (blood pressure [BP] and heart rate [HR]) in individuals with metabolic syndrome (MetS). Forty-four individuals were included in the study (control: 15) or in (WBV exercise: 29) groups. They were submitted to 3 bouts (1 minute each) of WBV exercise (5 Hz and peak-to-peak displacements of 2.5, 5.0, and 7.5 mm, corresponding to peak accelerations of 0.12, 0.25, and 0.35 g, respectively, sitting in a chair with the feet on the platform with knees flexed, followed by 1 minute of interset rest. The Control Group performed the same protocol, but the platform was turned off. The PL was measured through the visual analog pain scale, and the flexibility was measured through the anterior trunk flexion test. Significant improvements on PL ( P = .031) and flexibility ( P = .004) were found only in the WBV exercise group. The BP and HR remained at physiological levels. In conclusion, the WBV exercise would lead to physiological response decreasing PL and increasing flexibility as well as maintaining the cardiovascular responses in individuals with MetS.